2020
DOI: 10.1111/1759-7714.13612
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA CASC8 polymorphisms are associated with the risk of esophageal cancer in a Chinese population

Abstract: Background: Esophageal cancer (EC) is an important disease that threatens public health and safety. Although there are numerous treatment options for esophageal cancer including surgery, radiation therapy, and chemotherapy, these treatments have limited effects. Its morbidity and mortality vary widely among countries and regions. Esophageal cancer is classified into squamous cell carcinoma (ESCC) and esopheageal adenocarcinoma (EADC). Here, we examined the genetic susceptibility to ESCC in relation to function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Additionally, we verified the clinical significance of the four sARLNRs and found that the expression levels of CASC8 and AC015660.1 were significantly higher in PAAD cell lines and tumor tissues especially in patients with advanced grades and T-stages, while Z97832.2 and PAN3-AS1 were inverse. LncRNA-CASC8 polymorphisms have been demonstrated to increase the risk of esophageal cancer and lung adenocarcinoma [ 32 , 33 ], but the role in PAAD is first revealed in the present study. AC015660.1 was identified as a novel inflammation-related lncRNAs to predict the prognosis of gastric carcinoma patients [ 34 ], furthermore, we demonstrate its potential, as an angiogenesis-related lncRNA, for assessing PAAD prognosis here.…”
Section: Discussionmentioning
confidence: 59%
“…Additionally, we verified the clinical significance of the four sARLNRs and found that the expression levels of CASC8 and AC015660.1 were significantly higher in PAAD cell lines and tumor tissues especially in patients with advanced grades and T-stages, while Z97832.2 and PAN3-AS1 were inverse. LncRNA-CASC8 polymorphisms have been demonstrated to increase the risk of esophageal cancer and lung adenocarcinoma [ 32 , 33 ], but the role in PAAD is first revealed in the present study. AC015660.1 was identified as a novel inflammation-related lncRNAs to predict the prognosis of gastric carcinoma patients [ 34 ], furthermore, we demonstrate its potential, as an angiogenesis-related lncRNA, for assessing PAAD prognosis here.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, among central nervous system tumors, LINC01088 exerts pro-oncogenic activities in glioma via binding to SNRPA and regulating SNRPA mRNA transcription [ 37 ]. A previous study has proven the effect of the CASC8 rs1562430 polymorphism on esophageal squamous cell carcinoma (ESCC) susceptibility and discovered that functional polymorphisms in CASC8 rs1562430 A > G may influence an individual’s susceptibility to ESCC [ 38 ]. The USP21/YY1/SNHG16 axis is involved in the proliferation, migration, and invasion of non-small-cell lung cancer (NSCLC) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Huang et al ( 51 ) reported that overexpression of LINC01133 was associated with poorer prognosis in patients with PAAD and that the C/EBPβ-LINC01133 axis served an oncogenic function through upregulation of CCNG1. CASC8 was reported to be correlated with the progression of non-small cell lung cancer ( 52 ), retinoblastoma ( 53 ) and several other cancers ( 54 , 55 ). Upregulation of CASC8 was reported to be associated with the poor prognosis of patients with PAAD ( 56 ).…”
Section: Discussionmentioning
confidence: 99%